El efecto de la opinión pública en la política exterior de México: contrastando las teorías realistas y liberales - Morales Castillo, Rodrigo; Schiavon, Jorge A. (El Colegio de México A.C., 2015)
The preferences of the Mexican people with regard to interna- tional issues are stable and consistent over time. Even given the poor level of knowledge of international affairs, the difference in opinion between the best and least well informed Mexicans in minimum. There is a robust system of political beliefs that provides Mexicans with the conceptual tools to understand the complexity of global issues. Thus, Mexican foreign policy is attuned to the preferences of national opinion in conceptual terms; in addition, this may be seen as a valuable input when defining and implementing the country’s foreign policy.